Analysis of natural history of the diaphragmatic injury on the right in mice - Benedito Aparecido Caiel; Cristovam Scapulatempo Neto; Arthur Soares de Souza Júnior; Roberto Saad Júnior (Revista do Colégio Brasileiro de Cirurgiões)
Objective: to evaluate natural evolution of right diaphragmatic injury after the surgical removal of a portion from hemi diaphragm. Methods: the animals were submitted to a surgical removal of portion from right hemi diaphragm by median laparotomy. The sample consists of 42 animals being 2 animals from pilot project and 40 operated animals. And the variables of the study were herniation, liver protection, healing, persistent diaphragm injury, evaluation of 16 channels tomography and the variables "heart rate" and "weight". Results: we analyzed 40 mice, we had two post-operative deaths; we had 17 animals in this group suffered from herniation (42.5%) and 23 animals didn't suffer from herniation (57.5%). Analyzing the tomography as image method in the evaluation of diaphragmatic hernia, we had as a method with good sensitivity (78.6%), good specificity (90.9%), and good accuracy (86.1%) when compared to necropsy. Conclusion: there was a predominance of healing of right hemi diaphragm, the size of initial injury didn't have influence on occurrence of the liver protection or hernia in mice.